Programma: 20 november Buffalo Tom, Teenage Fanclub; 22 november Tribute to Little Walter; 23 november Bob Color; 26 november Kapanski Ensemble
Programma: 20 november Buffalo Tom, Teenage Fanclub; 22 november Tribute to Little Walter; 23 november Bob Color; 26 november Kapanski Ensemble.